Separator for lithium secondary battery and method for manufacturing same
By designing the distribution of inorganic particles of porous coating on the partitions of lithium secondary batteries, the problems of thermal shrinkage and uneven electrolyte wetting of large cylindrical lithium secondary batteries are solved, and the heat resistance and electrolyte permeability of the battery are improved. , reduces internal resistance and short circuit risks, and improves battery stability and energy density.
Patent Information
- Application Number
- CN202480002643.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-02-27
- Publication Date
- 2024-12-27
AI Technical Summary
The separators of large cylindrical lithium secondary batteries have problems such as insufficient thermal shrinkage characteristics and uneven electrolyte wetting, resulting in short circuits between electrodes and high resistance, affecting the performance and safety of the battery.
Using a separator with a porous polymer substrate, the surface coating includes a first area of a large number of inorganic particles and a second area of a small number of inorganic particles at both ends. The content ratio of inorganic particles is controlled by Equation 1 and Equation 2 to form a high The first region of porosity and the second region of low porosity improve heat resistance and electrolyte permeability of the separator.
It effectively reduces the thermal shrinkage characteristics of the separator, improves the wetting uniformity of the electrolyte, reduces the internal resistance of the battery and the risk of internal circuit short circuits, and improves the stability and energy density of the battery.
Smart Images

Figure CN119213622A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a separator for a lithium secondary battery and a method for manufacturing the same.
[0002] This application claims priority to Korean Patent Application No. 2023-0026319 filed in Korea on February 27, 2023 and Korean Patent Application No. 2023-0125131 filed on September 19, 2023, the disclosures of which are incorporated herein by reference. Background Art
[0003] Lithium secondary batteries are generally used not only in portable devices but also in electric vehicles (EV) or hybrid electric vehicles (HEV) powered by an electric power source due to easy applicability to various types of products and electrical characteristics such as high energy density.
[0004] The operating voltage of the unit cell of the currently widely used secondary battery is about 2.5V to 4.5V. Therefore, when a higher output voltage is required, a plurality of battery cells can be connected in series to form a battery pack. In addition, a battery pack can be formed by connecting a plurality of battery cells in parallel according to the required charge / discharge capacity of the battery pack. Therefore, the number of battery cells included in the battery pack and the type of electrical connection can be set differently according to the required output voltage and / or charge / discharge capacity.
[0005] Meanwhile, the types of unit cells of known secondary batteries include cylindrical, prismatic and pouch types. In the case of a cylindrical secondary battery cell, the battery is manufactured by winding the positive and negative electrodes with a separator or insulator between them to form a jellyroll-type electrode assembly, and placing the electrode assembly in a battery housing. In addition, the uncoated portion of each of the positive and negative electrodes can be connected to a strip-type electrode tab, and the electrode tab electrically connects the electrode assembly to the exposed electrode terminal. For reference, the positive terminal is a cover plate of a seal that seals the opening portion of the battery housing, and the negative terminal is a battery housing. However, conventional cylindrical battery cells with such a structure have high resistance and low current collection efficiency, and generate a lot of heat because the current is concentrated on the strip-type electrode tabs connected to the uncoated portion of the positive electrode and / or the uncoated portion of the negative electrode.
[0006] The resistance and heating issues are not serious for small cylindrical battery cells with 18650 or 21700 form factors, but as the form factors increase to apply cylindrical battery cells to electric vehicles, a large amount of heat may be generated near the electrode tabs during fast charging, and both end portions of the electrode assembly are squeezed by the shell due to repeated charge and discharge, causing partial deformation of the electrode assembly, resulting in tearing of the separator and internal circuit short circuit. The internal short circuit may cause the cylindrical battery cell to catch fire.
[0007] Attempts have been made to introduce a porous coating layer including inorganic particles into a separator to reduce the thermal shrinkage characteristics of a porous polymer substrate of the separator, but when a separator including a porous coating layer having the same composition over the entire surface is applied to a large cylindrical battery, heat resistance characteristics may still be limited.
[0008] Furthermore, in the case of thermal contraction of the separator, a circuit short circuit between the electrodes occurs, and due to the unique structure of the jelly roll, when an electrolyte solution is injected, it produces an uneven electrolyte wetting path and low electrolyte wetting uniformity, resulting in poor resistance in the battery. Summary of the invention
[0009] Technical issues
[0010] The present disclosure is directed to providing a separator having reduced heat shrinkage characteristics.
[0011] Specifically, the present disclosure is directed to providing a separator having improved heat resistance characteristics at both ends for a large cylindrical battery, and an electrochemical device including the same, particularly a lithium secondary battery.
[0012] Furthermore, the present disclosure aims to provide a separator with uniform electrolyte wetting for large cylindrical batteries, and an electrochemical device including the same, particularly a lithium secondary battery.
[0013] Furthermore, the present disclosure is directed to providing a cylindrical battery cell including a separator having reduced thermal shrinkage characteristics, a battery pack including the same, and a vehicle including the battery pack.
[0014] The technical problems to be solved by the present disclosure are not limited to the above-mentioned problems, and those skilled in the art will clearly understand these and other problems from the following description.
[0015] Technical Solution
[0016] In order to solve the above problems, the first aspect of the present disclosure provides:
[0017] A separator for an electrochemical device according to the following embodiment.
[0018] A separator for an electrochemical device according to a first embodiment includes:
[0019] a porous polymer substrate;
[0020] and a porous coating on at least one surface of the porous polymer substrate,
[0021] wherein the porous coating layer includes first regions at both ends on the outermost sides of the separator in the width direction and a second region between the first regions, and
[0022] wherein the first region and the second region each independently contain inorganic particles and a binder material, and a content ratio of the inorganic particles in the first region according to the following equation 1 is higher than a content ratio of the inorganic particles in the second region according to the following equation 2:
[0023] [Equation 1]
[0024] The content ratio of the inorganic particles in the first region (wt%) = [the amount of the inorganic particles in the first region / (the amount of the inorganic particles in the first region + the amount of the binder material in the first region)] × 100,
[0025] [Equation 2]
[0026] Content ratio of inorganic particles in the second region (wt%)=[amount of inorganic particles in the second region / (amount of inorganic particles in the second region+amount of binder material in the second region)]×100.
[0027] According to a second embodiment, in the first embodiment,
[0028] The porosity of the first region of the porous coating may be higher than the porosity of the second region.
[0029] According to a third embodiment, in the first or second embodiment,
[0030] The content ratio of the inorganic particles in the second region may be lower than that in the first region, and the content ratio of the inorganic particles in the second region may be 96 wt % or less.
[0031] According to a fourth embodiment, in any one of the first to third embodiments,
[0032] The content ratio of the inorganic particles in the first region may be higher than that in the second region, and the content ratio of the inorganic particles in the first region may be 70 wt % or more and 98 wt % or less.
[0033] According to a fifth embodiment, in any one of the first to fourth embodiments,
[0034] The width of one first region may be 5% to 35% of the total length of the porous coating layer in the width direction.
[0035] According to another embodiment of the present disclosure, a method for manufacturing a separator of the following embodiment is provided.
[0036] A method for producing a separator according to a sixth embodiment is a method for producing a separator according to any one of the first to fifth embodiments,
[0037] And the method is carried out by a roll-to-roll process in which a long strip of porous polymer substrate is continuously supplied, and comprises the following steps:
[0038] obtaining a separator strip comprising a composite porous coating having a first region and a second region on at least one surface of a porous polymer substrate,
[0039] The first regions having a predetermined width exist at both ends in a transverse direction (TD) perpendicular to a machine direction (MD) along which the porous polymer substrate travels, and the second region exists between the first regions.
[0040] According to a seventh embodiment, in the sixth embodiment,
[0041] The first region and the second region may be formed by applying a slurry for forming the first region and a slurry for forming the second region to respective predetermined regions using a double slot die.
[0042] According to an eighth embodiment, in the sixth or seventh embodiment,
[0043] The separator strips can be cut into predetermined lengths to obtain separators,
[0044] And the obtained separator has the second region, the side surfaces of which are exposed through both ends of the porous polymer substrate in the MD direction.
[0045] According to yet another embodiment of the present disclosure, an electrode assembly and a cylindrical battery cell are provided.
[0046] The electrode assembly according to the ninth embodiment is a jelly-roll type electrode assembly,
[0047] The jelly-roll type electrode assembly includes a first electrode plate having a sheet shape and a second electrode plate having a sheet shape, the first electrode plate and the second electrode plate being wound in one direction with a separator interposed therebetween,
[0048] wherein the separator is the separator according to any one of the first to fifth embodiments.
[0049] A cylindrical battery cell according to a tenth embodiment includes: a jelly-roll type electrode assembly,
[0050] The jelly roll type electrode assembly includes a positive electrode plate and a negative electrode plate, which are wound in one direction with a separator interposed therebetween; a battery case accommodating the electrode assembly; and a sealing body sealing an open end portion of the battery case,
[0051] wherein the separator is the separator according to any one of the first to fifth embodiments.
[0052] According to the eleventh embodiment, in the tenth embodiment,
[0053] The aspect ratio of a cylindrical battery cell may be 0.4 or greater.
[0054] According to a twelfth embodiment, in the tenth or eleventh embodiment,
[0055] The cylindrical battery cells may be 46110 cells, 48750 cells, 48110 cells, 48800 cells, 46800 cells or 46950 cells.
[0056] Beneficial Effects
[0057] A separator according to one aspect of the present disclosure has a porous coating layer on at least one surface of a porous polymer substrate, and the porous coating layer includes a first region including a large amount of inorganic particles at both ends to improve heat resistance at both ends of the separator.
[0058] Furthermore, first regions containing a large amount of inorganic particles are disposed at both ends, and second regions containing a small amount of inorganic particles are disposed between the first regions to improve wetting of electrolyte into the second regions through the first regions having high air permeability.
[0059] Therefore, according to another aspect of the present disclosure, a cylindrical battery cell having low internal resistance and no or almost no risk of internal circuit short circuit, and a battery pack and a vehicle including the same may be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 A separator according to one aspect of the present disclosure is schematically illustrated.
[0061] Figure 2 A method for manufacturing a separator according to one aspect of the present disclosure is schematically illustrated.
[0062] Figure 3 A method for manufacturing a separator according to one aspect of the present disclosure is schematically illustrated.
[0063] Figure 4 This is a photographic image of the negative electrode surface taken from the battery of Example 1.
[0064] Figure 5 This is a photographic image of the negative electrode surface taken from the battery of Example 2.
[0065] Figure 6 This is a photographic image of the negative electrode surface taken from the battery of Comparative Example 1. DETAILED DESCRIPTION
[0066] Hereinafter, the present disclosure will be described in detail.
[0067] It should be understood that, unless explicitly stated otherwise, when used in the specification, “include / comprising” specifies the presence of stated elements, and does not exclude the presence or addition of one or more other elements.
[0068] Throughout the specification, A and / or B means A or B or both.
[0069] One aspect of the present disclosure relates to a separator for an electrochemical device.
[0070] Electrochemical devices are devices that convert chemical energy into electrical energy through electrochemical reactions, and are concepts that include primary batteries and secondary batteries. In addition, secondary batteries can be charged and discharged, and are concepts that include lithium-ion batteries, nickel-cadmium batteries, nickel-hydrogen batteries, and the like.
[0071] In the present disclosure, the separator acts as a porous ion-conducting barrier in an electrochemical device that allows ions to pass through while preventing electrical contact between the negative electrode and the positive electrode. The separator has a plurality of pores therein, and preferably, the pores are connected to each other to allow gas and / or liquid to pass from one side of the separator to the opposite side.
[0072] The separator 100 according to one aspect of the present disclosure includes a porous polymer substrate 110 having a plurality of pores, and the polymer substrate 110 includes a polymer material. In addition, the separator includes a porous coating layer 120 on at least one surface of the polymer substrate 110 .
[0073] The porous coating layer may include inorganic particles and a binder material, and the inorganic particles may be bonded into a layered structure by the binder material. The coating layer has a porous structure generated by the space (interstitial volume) between the inorganic particles. The ability of the separator to retain the electrolyte solution may be improved by the porous structure.
[0074] In one embodiment of the present disclosure, the porous coating may be 3 to 40 volume % based on the total volume 100 volume % of the separator, and in addition or independently thereof, the thickness of the coating may be 5 to 50 % based on the total thickness 100 % of the separator.
[0075] In one embodiment of the present disclosure, the porous polymer substrate is a sheet-type porous membrane comprising a polymer material and having a plurality of holes. For example, the polymer substrate may include one or more sheets selected from at least one of a porous polymer membrane and a nonwoven fabric. The holes include open holes, and the open holes are connected to each other to allow gas and / or liquid to pass from one side of the polymer substrate to the opposite side thereof.
[0076] In one embodiment of the present disclosure, the polymer substrate may have a gas permeability of 2,000 sec / 100 cc or less and a porosity of 30% to 60% by volume in terms of output and cycle characteristics of the battery. Meanwhile, in the present disclosure, the pore size D of the polymer substrate is 50 It can be in the range of 10nm to 100nm.
[0077] In the present disclosure, air permeability refers to the time (seconds) required for 100 ml of air to pass through a polymer substrate or separator having a size of 1 square inch at a constant air pressure of 4.8 inches. Air permeability can be measured, for example, using Asahi seiko EG01-55-1MR.
[0078] In the present disclosure, porosity refers to the ratio of the volume occupied by pores to the total volume, expressed in volume %, and can be used interchangeably with void fraction, void ratio, etc. In the present disclosure, the measurement of porosity is not limited to a specific method, and according to one embodiment of the present disclosure, the porosity can be measured, for example, by the Brunauer-Emmett-Teller (BET) method or Hg porosimeter using nitrogen. Alternatively, in one embodiment of the present disclosure, the porosity of an object can be calculated by the difference between the apparent density and the net density of the object, wherein the net density is calculated by the density of the object (apparent density) and the composition ratio of the constituent elements of the object and the density of each constituent element.
[0079] Meanwhile, in one embodiment of the present disclosure, the porosity may increase with the amount of inorganic particles, so the porosity of the first region may be higher than the porosity of the second region. Meanwhile, the porosity may be measured, for example, by air permeability, so the air permeation time (seconds / 100cc) of the first region may be shorter than the air permeation time of the second region.
[0080] In one embodiment of the present disclosure, the thickness of the porous polymer substrate may be 5 μm to 20 μm to reduce the thickness of the electrochemical device and increase the energy density. When the thickness of the polymer substrate is below the above numerical range, the function of the conductive barrier is insufficient, and when the thickness of the polymer substrate exceeds the above range too much (that is, the polymer substrate is too thick), the resistance of the separator may increase too much.
[0081] In one embodiment of the present disclosure, the polymer material may preferably include a thermoplastic resin having a melting point of 200° C. or less to provide a shutdown function. The polymer material may include at least one of polyolefin-based resins. The shutdown function refers to a function in which the polymer resin melts when the battery temperature rises to block the pores of the polymer substrate to prevent ion movement between the positive electrode and the negative electrode, thereby preventing thermal runaway of the battery.
[0082] The polyolefin-based resin may include, for example, at least one selected from polyethylene, polypropylene, polybutylene, and polypentene. In particular, the polyolefin-based resin may be polyethylene and / or polypropylene. In addition, in addition to the polyolefin-based resin, the polymer material may also include at least one selected from polymer resins such as polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.
[0083] Subsequently, the inorganic particles and the binder material contained in the porous coating layer of the separator will be described.
[0084] In one embodiment of the present disclosure, the inorganic particles are not limited to a specific type and may include those having a particle size smaller than the desired thickness of the coating (e.g., 1 / 2 to 1 / 1,000 of the coating thickness) and possessing electrochemical stability. For example, the diameter of the inorganic particles may be 10 nm or greater. At the same time, for example, the average diameter D of the inorganic particles may be 50 The inorganic particles may be 10 μm or less, 7 μm or less, 5 μm or less, 2 μm or less, or 1 μm or less. That is, the inorganic particles are not limited to a specific type and may include particles within the operating voltage range of the applied electrochemical device (e.g., relative to Li / Li + Inorganic particles are those that do not undergo oxidation and / or reduction reactions within a range of 0V to 5V. In particular, the use of inorganic particles having the ability to transport ions can increase the ionic conductivity in electrochemical devices, thereby helping to improve performance. In addition, the use of high dielectric constant inorganic particles as inorganic particles can help to increase the dissociation degree of electrolyte salts such as lithium salts in liquid electrolytes, thereby improving the ionic conductivity of electrolyte solutions.
[0085] For the above reasons, in a specific embodiment of the present disclosure, the inorganic particles may include high dielectric constant inorganic particles having a dielectric constant of 5 or more or 10 or more, inorganic particles having the ability to transport lithium ions, or a mixture thereof. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more may include BaTiO used alone or in combination. 3 、Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr1-y Ti y O 3 (PLZT, where 0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -PbTiO 3 (PMN-PT), hafnium oxide (HfO 2 )、SrTiO 3 SnO 2 、CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 、Al 2 O 3 , SiC or TiO 2 In particular, inorganic particles such as BaTiO 3 、Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT, where 0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 ) 3 -PbTiO 3 (PMN-PT) or hafnium oxide (HfO 2 ) can exhibit high dielectric constant characteristics with a dielectric constant of 100 or more, and have piezoelectricity in which a potential difference occurs between two surfaces due to charges generated when stretched or compressed by applying a predetermined pressure, thereby preventing internal short circuits of two electrodes in the event of an external impact, which helps improve the safety of electrochemical devices. In addition, when high dielectric constant inorganic particles and inorganic particles having the ability to transport lithium ions are used together, their synergistic effect can be amplified.
[0086] In a specific embodiment of the present disclosure, the inorganic particles capable of transporting lithium ions refer to inorganic particles that contain lithium but do not store lithium and have the function of transporting lithium ions, and since the inorganic particles capable of transporting lithium ions can transport and move lithium ions due to certain defects in the particle structure, it is possible to improve the conduction of lithium ions in the battery, thereby helping to improve battery performance. Non-limiting examples of inorganic particles capable of transporting lithium ions may include: lithium phosphate (Li 3 PO 4 ); Lithium Titanium Phosphate (Li x Ti y (PO 4 )3 , where \(0 \lt x \lt 2\) and \(0 \lt y \lt 3\); lithium aluminum titanium phosphate \((Li x Al y Ti z (PO 4 ) 3 , where \(0 \lt x \lt 2\), \(0 \lt y \lt 1\), and \(0 \lt z \lt 3\); glass based on \((LiAlTiP) x O y \((0 \lt x \lt 4\) and \(0 \lt y \lt 13)\), such as \(14Li 2 O - 9Al 2 O 3 - 38TiO 2 - 39P 2 O 5 ; lithium lanthanum titanate \((Li x La y TiO 3 , where \(0 \lt x \lt 2\) and \(0 \lt y \lt 3\); lithium germanium thiophosphate \((Li x Ge y P z S w , where \(0 \lt x \lt 4\), \(0 \lt y \lt 1\), \(0 \lt z \lt 1\), and \(0 \lt w \lt 5\), such as \(Li 3.25 Ge 0.25 P 0.75 S 4 ; lithium nitride \((Li x N y , where \(0 \lt x \lt 4\) and \(0 \lt y \lt 2\), such as \(Li 3 N; glass based on SiS 2 \((Li x Si y S z , where \(0 \lt x \lt 3\), \(0 \lt y \lt 2\), and \(0 \lt z \lt 4\), such as \(Li 3 PO 4 - Li 2 S - SiS 2 ; or glass based on P 2 S 5 \((Li x P y S z , where \(0 \lt x \lt 3\), \(0 \lt y \lt 3\), and \(0 \lt z \lt 7\), such as \(LiI - Li 2 S - P 2 S 5 ; or a mixture thereof.
[0087] In one embodiment of the present disclosure, non-limiting examples of binder materials that can be used in the porous coating can include any polymer resin selected from the following: polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose, or a mixture thereof. However, the present disclosure is not limited thereto.
[0088] In the separator for an electrochemical device according to one embodiment of the present disclosure, the porous coating layer includes a first region and a second region. Specifically, the porous coating layer includes first regions at both ends on the outermost sides of the separator in the width direction and a second region between the first regions.
[0089] In one aspect of the present disclosure, the separator may have a rectangular shape. In this case, in the present specification, the long side of the separator may be referred to as the "length direction", and the short side of the separator may be referred to as the "width direction". In addition, when considering the process of manufacturing the separator, according to the process of manufacturing the separator, the long side of the separator may extend along the direction in which the separator travels, and the short side may extend in a direction perpendicular to the direction of travel. Therefore, the length direction of the separator may also be referred to as the machine direction (MD), and the width direction of the separator may also be referred to as the transverse direction (TD) perpendicular to the machine direction. At the same time, the machine direction and the transverse direction of the separator may be identified as the long side and the short side of the separator, and may also be identified by the polymer orientation of the separator substrate.
[0090] Figure 1 A separator 100 according to one embodiment of the present disclosure is shown.
[0091] Reference Figure 1 , a separator according to one embodiment of the present disclosure has a porous coating 120 on each of at least one surface (e.g., two surfaces) of a porous polymer substrate 110, and the porous coating includes a first region 122 at both outermost ends along the width direction and a second region 121 between the first regions.
[0092] In this case, the first region and the second region each independently contain inorganic particles and a binder material, and a content ratio of the inorganic particles in the first region according to Equation 1 is higher than a content ratio of the inorganic particles in the second region according to Equation 2.
[0093] [Equation 1]
[0094] Content ratio of inorganic particles in the first region (wt%) = [amount of inorganic particles in the first region / (amount of inorganic particles in the first region+amount of binder material in the first region)]×100
[0095] [Equation 2]
[0096] Content ratio of inorganic particles in the second region (wt%)=[amount of inorganic particles in the second region / (amount of inorganic particles in the second region+amount of binder material in the second region)]×100.
[0097] According to one embodiment of the present disclosure, since the porous coating layer includes a first region and a second region having inorganic particles of different content ratios, when the separator is provided to the electrode assembly, since the porosity of the first region is higher than that of the second region, it is possible to accelerate the penetration of the electrolyte into the second region through the first region, thereby reducing the internal resistance of the battery. In addition, when the separator is used to manufacture a cylindrical battery cell, it is possible to improve the heat resistance in the first region having a large amount of inorganic particles and suppress the shrinkage of the separator at both ends of the cylindrical battery cell, thereby preventing or suppressing an internal circuit short circuit in the battery.
[0098] In one embodiment of the present disclosure, the content ratio of inorganic particles in the second region is less than the content ratio of inorganic particles in the first region, and can be 96 wt % or less, 95 wt % or less, 90 wt % or less, 89 wt % or less, 85 wt % or less, 80 wt % or less, or 75 wt % or less. In one embodiment of the present disclosure, the content ratio of inorganic particles in the first region is greater than the content ratio of inorganic particles in the second region, and can be 60 wt % or more, 65 wt % or more, 70 wt % or more, 75 wt % or more, 80 wt % or more, 85 wt % or more, 88 wt % or more, 90 wt % or more, or 95 wt % or more. The content ratio of inorganic particles in the second region can be, for example, 60 wt % to 96 wt %, 70 wt % to 85 wt %, or 94 wt % to 95 wt %.
[0099] In one embodiment of the present disclosure, the content ratio of the inorganic particles in the first region is greater than the content ratio of the inorganic particles in the second region, and can be, for example, 70 wt % to 98 wt %, 75 wt % to 95 wt %, 77.5 wt % to 95 wt %, 80 wt % to 95 wt %, 80 wt % to 90 wt %, 77.5 wt % to 80 wt %, or 95 wt % to 98 wt %.
[0100] In one embodiment of the present disclosure, the width of the first region at both ends of the separator in the lateral direction can be adjusted according to the shape of the electrode (positive electrode and / or negative electrode) in the electrode assembly. For example, the width of one first region can be 0.1% to 40%, such as 5% to 35% or 10% to 30% of the total length of the porous coating in the lateral direction. When the width of the first region is within the above range, it is possible to improve the heat resistance at both ends of the separator and maintain the optimal weight of the separator, thereby improving the stability and energy density of the battery using the separator, but the present disclosure is not limited thereto.
[0101] Subsequently, various embodiments of the porous coating layer will be described by way of example. However, the disclosed embodiments are provided to help understand the present disclosure, and the scope of the present disclosure is not limited thereto.
[0102] In one embodiment of the present disclosure, the first region is arranged at a portion of the periphery of the second region so that at least a portion of the side of the second region is exposed to the outside. In addition, the first region is arranged so that the boundary abuts the second region. In a separator according to the present disclosure, the first region can be arranged to improve the heat resistance at both ends on the outermost side of the separator, and the first region can also be arranged to accelerate the penetration of the electrolyte into the coating.
[0103] Since the first region contains a small amount of binder resin and a large amount of inorganic particles, the first region has a higher porosity than the second region and a lower adhesion strength or bonding strength to the electrode than the second region, so that the electrolyte solution can more easily penetrate through the first region and reach the second region. At the same time, since the upper and lower surfaces of the separator contact the electrode when the battery is manufactured, electrolyte penetration occurs through the side of the separator. Therefore, in the case where the entire periphery of the second region is surrounded by the first region, the wetting of the electrolyte into the second region through the first region having a large amount of inorganic particles can be further improved. However, in the process of manufacturing the separator, the separator is manufactured in a long strip along the machine direction, so in order to make the process easy and reduce the total weight of the separator, it is preferred that the first region is formed on two opposite sides of the second region.
[0104] In a specific embodiment of the present disclosure, the second region may be disposed in a rectangular shape on the inner side of the surface of the polymer substrate, and the first region may be disposed on either side and each of the opposite sides of the second region, and the first region may not be disposed on the other two sides. When the first region is disposed as described above, it is possible to accelerate the direct penetration of the electrolyte into the second region through the side of the second region where the first region is not disposed, thereby reducing the internal resistance of the electrode assembly using the separator.
[0105] According to another aspect of the present disclosure, a method for manufacturing a separator is provided.
[0106] Figure 2 A schematic diagram showing a method for manufacturing a separator according to an embodiment of the present disclosure. Figure 2 A method for making a separator is described.
[0107] Reference Figure 2 , the separator can be manufactured by a roll-to-roll type continuous process. The long strip polymer substrate 110 is continuously fed by the rotating roller of the roll-to-roll machine, and the slurry for forming the coating is applied to the surface of the polymer substrate. The slurry can be applied by a common coating machine 300 such as a slot die. At the same time, a slurry can be prepared for each of the slurry for forming the first region and the slurry for forming the second region, and each slurry can be prepared by adding inorganic particles and a binder material to a suitable solvent.
[0108] When preparing each slurry, the slurry for forming the first region is applied to the two ends in the transverse direction (TD direction) perpendicular to the direction (MD direction) of the polymer substrate, and the slurry for forming the second region is applied between the first region. The slurry for forming the first region and the slurry for forming the second region can be applied simultaneously using a double slit die. Alternatively, the slurry can be applied in a sequential order by applying one of the slurry for forming the first region and the slurry for forming the second region, and then applying another slurry. For example, the slurry for forming the first region can be applied to the two ends of the polymer substrate in the width direction, and the slurry for forming the second region can be applied in a predetermined width inside the region where the slurry of the first region is continuously applied.
[0109] Subsequently, the applied slurry may be dried to obtain a separator strip including a composite coating having a first region and a second region. Drying may be performed by heat or air while passing through a dryer 500. Subsequently, the separator strip is cut into a predetermined width using, for example, a cutter 400 to obtain a separator, and in this case, in the obtained separator, the side of the second region is exposed through both ends of the polymer substrate in the traveling direction.
[0110] In one embodiment of the present disclosure, a porous coating layer may be formed on one surface of a porous polymer substrate in a sequential order, and then on another surface. Alternatively, a porous coating layer may be formed on both surfaces of a porous polymer substrate simultaneously in another manner. Subsequently, a separator obtained by slitting a separator strip to a desired length may be obtained in the shape of a strip to be applied to a cylindrical battery cell, thereby obtaining a separator in which the first region is disposed at both ends on the outermost long side of the porous coating layer and the second region is disposed between the first regions.
[0111] Figure 3 is a schematic diagram illustrating a method of manufacturing a separator according to another embodiment of the present disclosure.
[0112] Reference Figure 3 , a method for manufacturing a separator according to one embodiment of the present disclosure is as follows.
[0113] First, an uncut long strip of a porous polymer substrate 120 is prepared, and a slurry for forming a first region and a slurry for forming a second region, each containing inorganic particles and a binder material having a different amount of inorganic particles, are prepared. Subsequently, one or both surfaces of the porous polymer substrate are coated so that the first region 122 is disposed at both ends on the outermost side in the lateral direction, and the second region 121 and the first region 122 are arranged in an alternating manner therebetween, and then dried to form a porous coating 120. Subsequently, slitting is performed to cut into the desired width required for assembling a battery cell, thereby obtaining a separator having a porous coating including a first region having a large amount of inorganic particles at both ends on the outermost side in the lateral direction of the separator and a second region having a small amount of inorganic particles between the first regions.
[0114] According to another aspect of the present disclosure, an electrochemical device is provided, the electrochemical device comprising the above separator for an electrochemical device interposed between a positive electrode and a negative electrode. In one embodiment of the present disclosure, the electrochemical device may be a lithium ion secondary battery.
[0115] In a specific embodiment of the present disclosure, the electrochemical device can be manufactured by stacking the positive electrode and the negative electrode with a separator between the positive electrode and the negative electrode in a sequential order to form an electrode assembly, and if necessary, injecting a non-aqueous electrolyte solution. In this case, the positive electrode and the negative electrode of the electrode assembly and the non-aqueous electrolyte solution may include those commonly used in the manufacture of lithium secondary batteries.
[0116] In one embodiment of the present disclosure, the electrochemical device may be a cylindrical battery cell.
[0117] In one embodiment of the present disclosure, a cylindrical battery cell includes: a jelly-roll type electrode assembly having a structure in which a positive electrode plate and a negative electrode plate are wound in one direction with a separator interposed between the positive electrode plate and the negative electrode plate; a battery casing accommodating the electrode assembly; and a sealing body sealing an open end portion of the battery casing, and the separator is the separator described above.
[0118] In one embodiment of the present disclosure, the cylindrical battery cell may be a large cylindrical battery cell having an aspect ratio (defined as a value obtained by dividing the diameter of a cylindrical battery by its height, i.e., a ratio of diameter Φ to height H) of 0.4 or more.
[0119] In one embodiment of the present disclosure, the cylindrical battery cell may be, for example, a 46110 cell (46 mm in diameter, 110 mm in height, 0.418 aspect ratio), a 48750 cell (48 mm in diameter, 75 mm in height, 0.640 aspect ratio), a 48110 cell (48 mm in diameter, 110 mm in height, 0.418 aspect ratio), a 48800 cell (48 mm in diameter, 80 mm in height, 0.600 aspect ratio), a 46800 cell (46 mm in diameter, 80 mm in height, 0.575 aspect ratio), or a 46950 cell (46 mm in diameter, 95 mm in height, 0.484 aspect ratio). In the number representing the aspect ratio, the first two numbers represent the diameter of the cell, the next two numbers represent the height of the cell, and the last number O represents that the cross section of the cell is circular.
[0120] In one embodiment of the present disclosure, the electrode assembly may be a jelly roll type electrode assembly including a first electrode plate having a sheet shape and a second electrode plate having a sheet shape, the first electrode plate and the second electrode plate being wound in one direction with a separator interposed therebetween. In this case, the separator is the separator described above.
[0121] The first electrode plate and the second electrode plate may each be a positive electrode or a negative electrode, and an electrode assembly will be described below.
[0122] In a specific embodiment of the present disclosure, the positive electrode can be manufactured by forming a positive electrode material layer on a positive electrode current collector. The positive electrode material layer can be formed by coating a positive electrode slurry containing a positive electrode active material, a binder, a conductive material and a solvent on the positive electrode current collector, drying and rolling.
[0123] In a specific embodiment of the present disclosure, the positive electrode current collector may include, but is not limited to, any type of material having conductive properties without causing any chemical changes in the corresponding battery, such as stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel treated with carbon, nickel, titanium or silver on the surface.
[0124] In a specific embodiment of the present disclosure, the positive electrode active material may include a compound capable of reversibly intercalating and deintercalating lithium (lithiated intercalation compound).
[0125] In a specific embodiment of the present disclosure, the positive electrode active material may include, for example: lithium transition metal oxide; lithium metal iron phosphate; lithium nickel-manganese-cobalt oxide; oxides having partial substitution of other transition metals in lithium nickel-manganese-cobalt oxide; or two or more thereof, but not limited thereto. Specifically, the positive electrode active material may include, for example: layered compounds such as lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), or a compound substituted by one or more transition metals; Formula Li 1+x Mn 2-x O 4 (where x is 0 to 0.33), LiMnO 3 、LiMn 2 O 3 、LiMnO 2 Lithium manganese oxide; lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides such as LiV 3 O 8 ,LiV 3 O 4 、V 2 O 5 , Cu 2 V 2 O 7 ; LiNi 1-x M x O 2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, x = 0.01 to 0.3) represented by Ni site lithium nickel oxide; represented by the formula LiMn 2-x M x O 2 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 to 0.1) or Li 2 Mn 3 MO 8 (wherein M = Fe, Co, Ni, Cu or Zn) represented by lithium manganese composite oxide; lithium metal phosphate LiMPO 4 (wherein M = Fe, CO, Ni, or Mn); Lithium nickel-manganese-cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-x O 2 (x=0 to 0.03, a=0.3 to 0.95, b=0.01 to 0.35, c=0.01 to 0.5, a+b+c=1); Lithium nickel-manganese-cobalt oxide having partial substitution of aluminum a[Ni b Co c Mn d Al e 1-f M1 f O 2 (M1 is at least one selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, 0 ≤ f ≤ 0.1); an oxide having partial substitution of other transition metals in lithium nickel-manganese-cobalt oxide Li 1+x (Ni a Co b Mn c M d ) 1-x O 2 (x = 0 to 0.03, a = 0.3 to 0.95, b = 0.01 to 0.35, c = 0.01 to 0.5, d = 0.001 to 0.03, a + b + c + d = 1, M is any one selected from Fe, V, Cr, Ti, W, Ta, Mg, and Mo); a disulfide compound; Fe 2 (MoO 4 ) 3 , but not limited thereto.
[0126] In a specific embodiment of the present disclosure, optionally, the positive electrode may further include a conductive material. The conductive material may be porous. Thus, the conductive material may include, but not be limited to, any material having porous and conductive properties, and may include, for example, carbon-based materials having porous properties. The carbon-based materials may include carbon black, graphite, graphene, activated carbon, carbon fiber, and carbon nanotubes (CNT). In addition, the conductive material may include: metal conductive materials, such as metal fibers, metal meshes; metal powders, such as copper, silver, nickel, aluminum; or organic conductive materials, such as polyphenylene derivatives. These conductive materials may be used alone or in combination.
[0127] In a specific embodiment of the present disclosure, optionally, the positive electrode can also include a binder. The binder can include a thermoplastic resin or a thermosetting resin. More specifically, the binder can include polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene-butadiene rubber, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer, polychlorotrifluoroethylene, polyvinylidene fluoride-pentafluoropropylene copolymer, propylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, polyvinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene copolymer and ethylene-acrylic acid copolymer, but not limited thereto, and can include any type of binder used in the corresponding technical field.
[0128] In a specific embodiment of the present disclosure, the positive electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of solids in the positive electrode slurry.
[0129] In a specific embodiment of the present disclosure, the solvent used in the positive electrode slurry may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and when the positive electrode active material and optional binder and conductive material are included, the solvent may be used in an amount sufficient for the desired viscosity. For example, the solvent may be included in an amount such that the concentration of solids in the slurry containing the positive electrode active material and optional binder and conductive material is 50% to 95% by weight, and preferably 70% to 90% by weight.
[0130] In a specific embodiment of the present disclosure, the positive electrode can be manufactured by mixing a positive electrode active material and an optional conductive material and an optional binder to prepare a composition for forming a positive electrode active material layer, applying the composition to at least one surface of a positive electrode current collector, drying and calendering. Another method for manufacturing a positive electrode may include casting the composition for forming a positive electrode active material layer on a carrier, peeling the film from the carrier, and laminating the film on the positive electrode current collector.
[0131] In a specific embodiment of the present disclosure, the negative electrode can be manufactured by forming a negative electrode material layer on a negative electrode current collector. The negative electrode material layer can be formed by coating a negative electrode slurry containing a negative electrode active material, a binder, a conductive material and a solvent on the negative electrode current collector, drying and rolling.
[0132] In a specific embodiment of the present disclosure, the negative electrode active material may include lithium metal, a carbon material capable of reversibly inserting / extracting lithium ions, a metal or an alloy of a metal and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, or a transition metal oxide, or a mixture thereof.
[0133] The carbon material capable of reversibly inserting / extracting lithium ions as an example of the negative electrode active material may include, but is not limited to, any type of carbon-based negative electrode active material commonly used in lithium ion secondary batteries, and typical examples thereof may include at least one of crystalline carbon or amorphous carbon, or a combination of these. Examples of crystalline carbon may include graphite, such as amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, and examples of amorphous carbon may include soft carbon (low-temperature sintered carbon) or hard carbon, mesophase pitch carbide and sintered coke.
[0134] The metal or an alloy of a metal and lithium as an example of the negative electrode active material may include Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, or a mixture thereof, or an alloy of these metals and lithium.
[0135] The metal composite oxide as an example of the negative electrode active material may include PbO, PbO 2 、Pb 2 O 3 、Pb 3 O 4 、Sb 2 O 3 、Sb 2 O 4 、Sb 2 O 5 、GeO、GeO 2 、Bi 2 O 3 、Bi 2 O 4 、Bi 2 O 5 、Li x Fe 2 O 3 (0≤x≤1), Li x WO 2 (0≤x≤1), or Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2 and Group 3 elements in the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), or a mixture thereof.
[0136] Materials capable of doping and de-doping lithium as examples of the negative electrode active material may include Si, SiO x (0 < x ≤ 2), Si-Y alloy (Y is at least one of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, or a rare earth element, or a mixture thereof, but not Si), Sn, SnO 2 、Sn-Y (Y is at least one of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a mixture thereof, but not Sn), and at least one of them can be mixed with SiO 2 Y may include Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a mixture thereof.
[0137] Transition metal oxides as examples of the negative electrode active material may include lithium-containing titanium composite oxide (LTO), vanadium oxide, and lithium vanadium oxide.
[0138] In a specific embodiment of the present disclosure, based on the total weight of the solids in the negative electrode slurry, the negative electrode active material may be included in an amount of 80% to 99% by weight.
[0139] In a specific embodiment of the present disclosure, optionally, the negative electrode may further include a binder. The binder is a component that helps the adhesion between the active material and the current collector or among the active material, the conductive material, and the current collector, and is usually added in an amount of 1% to 30% by weight based on the total weight of the solids in the negative electrode slurry. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and their copolymers.
[0140] In a specific embodiment of the present disclosure, optionally, the negative electrode may further include a conductive material. The conductive material is a component for improving the conductivity of the negative electrode active material, and may be added in an amount of 1% to 20% by weight based on the total weight of the solids in the negative electrode slurry. The conductive material may be the same or different from the conductive material used to make the positive electrode, and may include, for example, carbon black, acetylene black (or Denka black), Ketjen black, channel black, furnace black, lamp black or thermal black carbon powder; graphite powder with a well-formed crystalline structure, such as natural graphite, artificial graphite or graphite; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as carbon fluoride, aluminum and nickel powder; conductive whiskers, such as zinc oxide, potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0141] In a specific embodiment of the present disclosure, the solvent used in the negative electrode slurry may include water or an organic solvent such as NMP or alcohol, and when the negative electrode active material and optional binder and conductive material are included, the solvent may be used in an amount sufficient for the desired viscosity. For example, the solvent may be included in an amount such that the concentration of solids in the slurry containing the negative electrode active material and optional binder and conductive material is 50 wt % to 95 wt %, and preferably 70 wt % to 90 wt %.
[0142] In a specific embodiment of the present disclosure, when a non-aqueous electrolyte solution is used, the non-aqueous electrolyte solution may include a lithium salt and an organic solvent, and may further include additives commonly used in the corresponding technical field.
[0143] In one embodiment of the present disclosure, the lithium salt has a cation and an anion, wherein the cation may include Li + , and the anions may include F - , Cl - Br - ,I - 、NO 3 - 、N(CN) 2 - , ClO 4 - , BF 4 - 、AlO 4 - 、AlCl 4 - PF 6 - , SbF 6 - , AsF 6 - , BF 2 C2 O 4 - 、BC 4 O 8 - 、(CF 3 ) 2 PF 4 - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、CF 3 SO 3 - 、C 4 F 9 SO 3 - 、CF 3 CF 2 SO 3 - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH - 、(SF 5 ) 3 C - 、(CF 3 SO 2 ) 3 C - 、CF 3 (CF 2 ) 7 SO 3 - 、CF 3 CO 2 - 、CH 3 CO2 - 、SCN - ,(CF 3 CF 2 SO 2 ) 2 N - , or a mixture thereof.
[0144] In a specific embodiment of the present disclosure, exemplary lithium salts can be used alone or in combination as needed. The lithium salt can be included in the non-aqueous electrolyte solution at a concentration of 0.01M to 5M, or 0.1M to 5M, or 0.1M to 3M, and the concentration can be appropriately changed within a commonly used range.
[0145] In a specific embodiment of the present disclosure, the organic solvent may include any type of organic solvent that can minimize oxidation-induced decomposition during charging and discharging of the secondary battery and exert the expected properties together with the additive. For example, the organic solvent may include an ether-based solvent, an ester-based solvent, or an amide-based solvent used alone or in combination.
[0146] In a specific embodiment of the present disclosure, among exemplary organic solvents, the ether-based solvent may include dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, or a mixture thereof, but is not limited thereto.
[0147] In a specific embodiment of the present disclosure, the ester-based solvent may include a cyclic carbonate compound, a linear carbonate compound, a linear ester compound, a cyclic ester compound, or a mixture thereof.
[0148] In a specific embodiment of the present disclosure, specific examples of the cyclic carbonate compound may include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, fluoroethylene carbonate (FEC), or a mixture thereof.
[0149] In a specific embodiment of the present disclosure, specific examples of the linear carbonate compound may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, or a mixture thereof, but are not limited thereto.
[0150] In a specific embodiment of the present disclosure, specific examples of the linear ester compound may typically include methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, or a mixture thereof, but are not limited thereto.
[0151] In a specific embodiment of the present disclosure, specific examples of the cyclic ester compound may include γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, ε-caprolactone, or a mixture thereof, but are not limited thereto.
[0152] In a specific embodiment of the present disclosure, the cyclic carbonate-based compound is a high viscosity organic solvent, and thus the lithium salt is well dissolved in the electrolyte due to the high dielectric constant. Therefore, the cyclic carbonate-based compound can be mixed with a linear carbonate-based compound such as dimethyl carbonate and diethyl carbonate having low viscosity and low dielectric constant and a linear ester-based compound in an optimal ratio to prepare a non-aqueous electrolyte solution with high conductivity.
[0153] According to an aspect of the present disclosure, a separator for a lithium secondary battery can realize the effective transmission of lithium ions, reduce the side reaction at the interface between the separator for a lithium secondary battery containing an ion-conducting polymer material and an electrode, and significantly reduce the increase in the initial internal resistance of the battery. As a result, the battery using the separator has improved output density characteristics and a reduction in irreversible capacity and its improved rate characteristics, so it is possible to reduce the time required to charge or discharge the battery and improve the charge and discharge life. Therefore, it can be used in industrial fields that require fast charging, for example, mobile devices include mobile phones, laptop computers, digital cameras, video cameras, or electric vehicles include hybrid electric vehicles (HEV), plug-in HEV (PHEV), and medium and large energy storage systems.
[0154] In particular, the separator having the porous coating layer as described above may have improved heat resistance at both ends on the outermost sides, and thus may be used for a large cylindrical battery cell.
[0155] Hereinafter, embodiments, comparative examples and experimental examples are provided to help understand the present disclosure. However, the following experimental examples are experimental examples regarding the configuration and effects of the present disclosure, and the protection scope and effects of the present disclosure are not limited thereto.
[0156] [Manufacturing of separator]
[0157] Example 1
[0158] PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone in a weight ratio of 22.5:77.5 to prepare a first region-forming slurry containing 20 wt % solids.
[0159] Subsequently, PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 25:75 to prepare a second region-forming slurry containing 20 wt % solids.
[0160] A polymer film made of polyethylene (thickness 9 μm, porosity 45% by volume, air permeability 60 seconds / 100 cc) was prepared and Figure 1 The shape shown applied the first region forming slurry and the second region forming slurry in sequential order and dried at 23° C. under a humidity condition of 45% relative humidity to obtain a separator. The total width of the separator was 200 mm, and the width of the first region on each of both sides was 60 mm.
[0161] Example 2
[0162] PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 20:80 to prepare a first region-forming slurry containing 20 wt % solids.
[0163] Subsequently, PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 25:75 to prepare a second region-forming slurry containing 20 wt % solids.
[0164] A polymer film made of polyethylene (thickness 9 μm, porosity 45% by volume, air permeability 60 seconds / 100 cc) was prepared and Figure 1 The shape shown applied the first region forming slurry and the second region forming slurry in sequential order and dried at 23° C. under a humidity condition of 45% relative humidity to obtain a separator. The total width of the separator was 200 mm, and the width of the first region on each of both sides was 60 mm.
[0165] Example 3
[0166] PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 5:95 to prepare a first region-forming slurry containing 20 wt % solids.
[0167] Subsequently, PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 25:75 to prepare a second region-forming slurry containing 20 wt % solids.
[0168] A polymer film made of polyethylene (thickness 9 μm, porosity 45% by volume, air permeability 60 seconds / 100 cc) was prepared and Figure 1 The shape shown applied the first region forming slurry and the second region forming slurry in sequential order and dried at 23° C. under a humidity condition of 45% relative humidity to obtain a separator. The total width of the separator was 200 mm, and the width of the first region on each of both sides was 60 mm.
[0169] Comparative Example 1
[0170] PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 25:75 to prepare a coating-forming slurry containing 20 wt % solids.
[0171] A polymer film made of polyethylene (thickness 9 μm, porosity 45% by volume, air permeation time 60 sec / 100 cc) was prepared, and the slurry was applied and dried at 23° C. under humidity conditions of 45% relative humidity to obtain a separator. The total width of the separator was 200 mm.
[0172] Comparative Example 2
[0173] PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 25:75 to prepare a first region-forming slurry containing 20 wt % solids.
[0174] Subsequently, PVDF-HFP (molecular weight (Mw) 500,000 g / mol, HFP content 15 wt %) and alumina (particle size 0.5 μm) were added to acetone at a weight ratio of 5:95 to prepare a second region-forming slurry containing 20 wt % solids.
[0175] A polymer film made of polyethylene (thickness 9 μm, porosity 45% by volume, air permeability 60 seconds / 100 cc) was prepared and Figure 1 The shape shown applied the first region forming slurry and the second region forming slurry in sequential order and dried at 23° C. under a humidity condition of 45% relative humidity to obtain a separator. The total width of the separator was 200 mm, and the width of the first region on each of both sides was 60 mm.
[0176] [Evaluation of separator characteristics]
[0177] The characteristics of the separator were evaluated by the evaluation method described below, and the results are shown in the following Tables 1 and Figures 3 to 5 middle.
[0178] Evaluation Methodology
[0179] Heat resistance
[0180] A spacer having a length of 200 mm and a width of 200 mm was prepared, marked with dots at intervals of 20 mm in the horizontal and vertical directions, and then left to stand in an oven at 130° C. for 30 minutes, and changes in the intervals between the dots were observed.
[0181] The interval variation between points in the first region and the second region was measured in each of the length direction and the width direction, and the shrinkage rate of the separator was measured according to the following equation.
[0182] In the following equation, after the sample is left standing in an oven, the “interval between points” is measured using a ruler, the measurement is performed for each of the first region and the second region, and the shrinkage rate is calculated by averaging the measured values in the respective regions.
[0183] Shrinkage rate (%) = [(20 mm - interval between points (mm)) / 20 mm] × 100
[0184] Breathing time
[0185] According to JIS P8117, the air permeability of the separator was measured using an air permeability measuring instrument (Asahi Seiko, EGO-IT). Meanwhile, in order to measure the air permeability of each of the first region and the second region, after preparing the separator, a knife was used to separate the separator into the first region and the second region to obtain a sample for air permeability time measurement.
[0186] Electrode adhesion strength
[0187] The active material [natural graphite and artificial graphite (weight ratio 5:5)], the conductive material [super P], and the binder [polyvinylidene fluoride (PVdF)] were mixed and dispersed in water at a weight ratio of 92:2:6, and then coated on a copper foil with a width of 250 mm to manufacture a negative electrode.
[0188] The separator produced in each of Examples 1 to 3 and Comparative Examples 1 and 2 was prepared.
[0189] The prepared separator was divided into a first region and a second region using a knife.
[0190] The prepared separator and negative electrode were stacked and interposed between 100 μm thick PET films, and then adhered using a roll laminator. In this case, the conditions of the roll laminator were 60° C., a pressure of 2.4 kgf / mm, and a rate of 5 m / min.
[0191] The separator and the negative electrode adhered to each other were cut into a width of 25 mm and a length of 70 mm, the ends of the separator and the negative electrode were mounted on a UTM machine (Instron), a force was applied at a measuring rate of 300 mm / min at 180° to separate the separator from the negative electrode, and the force required for peeling was measured.
[0192] As can be seen from Table 1 above, it was determined that when each of the separators of Example 3 and Comparative Example 2 was used, the electrode assembly was poor due to low adhesion strength in the second region or the first region, which was not suitable for evaluating electrolyte wetting, and therefore the electrolyte wetting evaluation results were omitted.
[0193] Evaluation of electrolyte wetting
[0194] (1) Manufacturing of negative electrode
[0195] Artificial graphite as a negative electrode active material, carbon black as a conductive material, carboxymethyl cellulose (CMC) as a dispersant, and styrene butadiene rubber (SBR, Zeon BM-L301) as a binder were mixed with water at a weight ratio of 95.8:1:1.2:2 to prepare a negative electrode slurry. The negative electrode slurry was coated on a copper foil (Cu foil) with a thickness of 50 μm to form a thin electrode plate, and the electrode plate was dried at 135° C. for 3 hours or more and rolled (pressed) to manufacture a negative electrode.
[0196] (2) Manufacturing of positive electrode
[0197] LiCoO as the positive electrode active material 2 , carbon black as a conductive material and polyvinylidene fluoride (PVDF) as a binder were mixed with N-methyl-2-pyrrolidone (NMP) at a weight ratio of 98:1:1 to prepare a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil with a thickness of 20 μm to form a thin electrode plate, and the electrode plate was dried at 135°C for 3 hours or more and rolled (pressed) to manufacture a positive electrode.
[0198] (3) Manufacturing of lithium secondary batteries
[0199] Subsequently, the negative electrode and the positive electrode were stacked together with a separator interposed therebetween to prepare a stacked electrode assembly, and the electrode assembly was placed in a bag-shaped case, into which 1M LiPF 6An electrolyte solution was dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 30:70 to manufacture a lithium secondary battery.
[0200] After disassembling the prepared secondary battery at SOC 60, wetting was observed by negative electrode surface observation. When wetting was good, a uniform charge state ( Figure 4 and Figure 5 ), but when wetting is poor, uncharged dark parts are observed on the negative electrode surface ( Figure 6 ).
[0201] Evaluation results
[0202] [Table 1]
[0203]
[0204] [Table 2]
[0205]
[0206] As can be seen from the above results, it was determined that when the first region having a large amount of inorganic particles existed on both sides of the separator, the heat resistance at the side of the separator was improved.
[0207] Therefore, when the separator is applied to a jelly-roll type electrode assembly and used in a cylindrical battery, it is expected to solve the problem of internal circuit short circuit caused by shrinkage at both ends of the separator.
[0208] Although the present disclosure has been described above with respect to a limited number of embodiments and drawings, the present disclosure is not limited thereto, and it is apparent that those skilled in the art may make various changes and modifications within the technical aspects of the present disclosure and the scope of the appended claims and their equivalents.
[0209] [Explanation of Reference Numerals]
[0210] 100-Separator
[0211] 110-Porous polymer substrate
[0212] 120-Porous coating
[0213] 121-Second area, 122-First area
[0214] 300-Coating Machine
[0215] 400-cutting machine
[0216] 500-Dryer
Claims
1. A separator for an electrochemical device, comprising: a porous polymer substrate; and a porous coating on at least one surface of the porous polymer substrate, wherein the porous coating layer includes first regions at both ends on the outermost sides of the separator in the width direction and a second region between the first regions, and wherein the first region and the second region each independently contain inorganic particles and a binder material, and a content ratio of the inorganic particles in the first region according to the following equation 1 is higher than a content ratio of the inorganic particles in the second region according to the following equation 2: [Equation 1] The content ratio of the inorganic particles in the first region (weight %)=[the amount of the inorganic particles in the first region / (the amount of the inorganic particles in the first region+the amount of the binder material in the first region)]×100, [Equation 2] The content ratio of the inorganic particles in the second region (weight %)=[the amount of the inorganic particles in the second region / (the amount of the inorganic particles in the second region+the amount of the binder material in the second region)]×100. 2 . The separator for an electrochemical device according to claim 1 , wherein the porosity of the first region of the porous coating layer is higher than the porosity of the second region. 3 . The separator for an electrochemical device according to claim 1 , wherein a content ratio of the inorganic particles in the second region is lower than that in the first region, and a content ratio of the inorganic particles in the second region is 96 wt % or less. 4 . The separator for an electrochemical device according to claim 1 , wherein a content ratio of the inorganic particles in the first region is higher than that in the second region, and a content ratio of the inorganic particles in the first region is 70 wt % or more and 98 wt % or less. 5 . The separator for an electrochemical device according to claim 1 , wherein a width of one first region is 5% to 35% of a total length of the porous coating layer in the width direction.
6. A method for manufacturing a separator according to any one of claims 1 to 5, wherein the method is performed by a roll-to-roll process in which a long strip of porous polymer substrate is continuously supplied, and The method comprises: A separator strip is obtained comprising a composite porous coating having a first region and a second region on at least one surface of the porous polymer substrate, wherein the first region having a predetermined width is present at both ends in a transverse direction (TD) perpendicular to a machine direction (MD) along which the porous polymer substrate travels, and the second region is present between the first regions. 7 . The method for manufacturing a separator according to claim 6 , wherein the first region and the second region are formed by applying a slurry for forming the first region and a slurry for forming the second region to respective predetermined regions using a double slit die.
8. The method for manufacturing a separator according to claim 6, wherein the separator strip is cut into a predetermined length to obtain the separator, and The obtained separator has the second region, and the side surfaces of the second region are exposed through both ends of the porous polymer substrate in the MD direction.
9. A jelly roll type electrode assembly comprising: a first electrode plate having a sheet shape and a second electrode plate having a sheet shape, the first electrode plate and the second electrode plate being wound in one direction with a separator interposed therebetween, The separator is according to any one of claims 1 to 5.
10. A cylindrical battery cell comprising: A jelly roll type electrode assembly, the jelly roll type electrode assembly comprising a positive electrode plate and a negative electrode plate, the positive electrode plate and the negative electrode plate being wound in one direction with a separator interposed between the positive electrode plate and the negative electrode plate; a battery case accommodating the electrode assembly; and a sealing body sealing an open end portion of the battery case, The separator is according to any one of claims 1 to 5. 11 . The cylindrical battery cell according to claim 10 , wherein an aspect ratio of the cylindrical battery cell is 0.4 or greater.
12. The cylindrical battery cell of claim 10, wherein the cylindrical battery cell is a 46110 cell, a 48750 cell, a 48110 cell, a 48800 cell, a 46800 cell, or a 46950 cell.